The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12866-017-0987-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a genus-specific next generation sequencing approach for sensitive and quantitative determination of the Legionella microbiome in freshwater systems

Abstract: BackgroundNext Generation Sequencing (NGS) has revolutionized the analysis of natural and man-made microbial communities by using universal primers for bacteria in a PCR based approach targeting the 16S rRNA gene. In our study we narrowed primer specificity to a single, monophyletic genus because for many questions in microbiology only a specific part of the whole microbiome is of interest. We have chosen the genus Legionella, comprising more than 20 pathogenic species, due to its high relevance for water-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
5
26
0
Order By: Relevance
“…For example, Pereira et al. () tested a universal primer targeting Legionella pneumophila V4 and V5 16S rRNA regions in spiked drinking and nuclease‐free water in 10‐fold dilutions for comparative NGS analysis. The authors found NGS reads of eDNA mock communities (a mixture of six different Legionella sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pereira et al. () tested a universal primer targeting Legionella pneumophila V4 and V5 16S rRNA regions in spiked drinking and nuclease‐free water in 10‐fold dilutions for comparative NGS analysis. The authors found NGS reads of eDNA mock communities (a mixture of six different Legionella sp.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting highly conserved regions that flank polymorphic regions (Thomsen & Willerslev, ) for PCR primer design, NGS of the resulting amplicons can be used for metabarcoding of the whole community, with a high likelihood of detecting cryptic, elusive or rare species that are often missed using capture or observation‐based methods (Evans et al., ; Pompanon, Coissac, & Taberlet, ; Port et al., ; Valentini et al., ). This method of metabarcoding has also been shown to be semiquantitative when using spiked samples and spiked communities (Diaz‐Real ; Pereira, Peplies, Brettar, & Höfle, ).…”
Section: Introductionmentioning
confidence: 99%
“…This hindrance may be overcome with the application of newly designed technologies for high-throughput sequencing and bioinformatics investigations of obtained sequences. The increasingly used in environmental microbiology studies Next Generation Sequencing (NGS) approach becomes more available and allows to gain seemingly more information of tested sample [66][67][68]. However, as indicated in this study, the successful implementation of NGS in tap water samples research requires proven, reliable and reproductive procedures of highefficiency DNA extraction from this medium.…”
Section: Considered Solutionsmentioning
confidence: 94%
“…WHO guidelines briefly mention the issue of hot tap water quality, indicating that hot tap water systems should be designed to minimise the proliferation of Legionella [5]. To date, several studies considered the bacterial biodiversity and microbial contamination in hot tap water samples [13][14][15][16]. The majority of them focus on the presence of genus Legionella.…”
Section: Introductionmentioning
confidence: 99%